PENGARUH KOMPENSASI MANAJEMEN, PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Industri Dasar dan Kimia di Bursa Efek Indonesia (BEI) tahun 2012-2016) - Komala Sari, Sri Ratna; Kennedy, Kennedy; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Earnings management is a disclosure of management asa a means of direct management intervention in the financial reporting processing of income or profits with a view to obtaining benefits or benefits tersmantu for managers or companies based on economic factors. The purpose of this research is to test : 1) the effect of management compensation on earnings management, 2) the effect of tax planning on earnings management, 3) the effect of deferred tax expense on earnings management. The object of this research is the basic industrial and chemical companies listed on BEI with the period of observation 2012-2016. Sample selection using purposive sampling technique. The data used in this research is secondary data collected by taking data on the annual financial statements of the company throught the website www.idx.co.id. the data analysis technique used is multiple linear analysis using the help os SPSS 17.0 program. The results of the research found that : 1) management compensation does not affect the earnings management. 2) tax lanning does not affect the earnings management. 3) the deferred tax expense does not affect the earnings management. With the effect of (R2) is 0,110 atau 11%. It means that 11% earnings management is influenced by independent variable that is management compensation, tax planning and deferred tax expense, while 89% is explained by other variable not examined in this researchKeyword : Management Compensation, Tax Planning, Deferred Tax Expense, Earnings Management